Plyometric anatomy - Hansen, Derek 1969-; Kennelly, Steve (Human Kinetics, 2017)
In Plyometric Anatomy, authors Derek Hansen and Steve Kennelly share the training they have used to propel athletes at all levels to success. Together they detail 94 plyometric exercises, along with 78 variations that increase in difficulty for continued development over time. With content on bilateral exercises, unilateral exercises, core exercises, and plyometric combinations, it's all here.